Dampak Serta Efektifitas Pembelajaran Edutainment Anak Usia Dini di Lab School Audifa - Zulkarnain, Nur Fitriya; Mumtadzah, Ardhe Rizka; Asiyah, Asiyah (STAI Bumi Silampari, 2023)
Early childhood edutainment learning has emerged as a promising pedagogical approach that integrates education and entertainment to promote holistic development in young children. This study explores the impact and effectiveness of early childhood edutainment learning at the Audifa Lab School, a leading early childhood education institution in Indonesia. The study employed a mixed-methods approach, combining quantitative and qualitative data collection methods, to comprehensively assess the outcomes of the school's edutainment-based curriculum. Quantitative data were collected through standardized assessments of children's cognitive, social, and emotional development. These assessments revealed significant improvements in children's language skills, literacy development, numeracy skills, problem-solving abilities, and creativity. Moreover, children demonstrated enhanced social-emotional development, exhibiting greater self-regulation, empathy, and cooperation. Qualitative data were gathered through observations of classroom interactions, teacher interviews, and parent surveys. These findings provided rich insights into the implementation of edutainment activities and the positive impact they had on children's engagement, motivation, and overall learning experience. Teachers reported that edutainment approaches fostered a joyful and stimulating learning environment, leading to increased participation, curiosity, and a love of learning among children. Parents expressed satisfaction with the school's edutainment-based curriculum, noting their children's positive academic progress, social growth, and overall well-being.The study's findings underscore the effectiveness of early childhood edutainment learning in promoting holistic child development. The Audifa Lab School's success in implementing edutainment approaches provides a valuable model for other early childhood education settings. The study concludes by recommending strategies for effective implementation of edutainment programs, emphasizing the importance of age-appropriateness, individualization, and the integration of multiple learning modalities.